(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Emotional bias is the term used to describe how people express their feelings about acting in a particular way. It affects how people behave, and conduct in turn affects the choices made by individual investors. The impact of emotional biases on the equities investment decisions of individual investors is the main topic of this study. Everyone believed for a long time that traditional finance theory was correct since it said that investors utilize economic models or various estimates to make educated decisions. According to the investment theories, investors are logical beings that make decisions based on limiting risks and optimizing returns. Loss aversion, overconfidence, endowment, self-control, regret aversion, and status quo biases are markers of emotional biases. Research indicates that the biases against loss aversion, overconfidence, self-control, and remorse had a strong positive influence on decisions regarding investing in stock none of the less, prejudice stemming from endowments and the status quo did not significantly influence the stock investment choices of individual investors. When making financial decisions, decision-makers may be influenced by certain biases. This research adds to the existing knowledge on behavioral finance and assists investors in identifying and reducing bias in their investment decisions.This study examines the impact of Emotional biases on investment decisions and the types of investors involved.